2007
DOI: 10.2298/apt0738149r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different conditions on Cu(II) and Cr(VI) biosorption by dried waste tea fungal biomass

Abstract: Some industrial wastewaters contain high quantities of non-toxic salts besides heavy metal ions. The presence of salt ions leads to a high ionic strength of water, which may significantly affect the performance of the biosorption process, so that the effect of salts on the biosorption of heavy metal ions should be investigated. In this study the effect of different salts concentrations (0.1; 0.5 and 1 mol L-1) and dosage of tea fungal biomass (0.15; 0.25 and 0.5 g L-1) dried at different temperatures: 20°C, 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Various biosorbents have been tried, which include seaweeds, moulds, yeast, bacteria, crab shells, agricultural products such modified corn stalks, (Chen et al, 2011), hazelnut shell (Cimino et al, 2000), orange waste (Perez-Marin et al, 2007) and tamarind peel (Acosta et al, 2010). It has also been reported that some of these biomass can reduce chromium (VI) to chromium (III), like tamarind peel (Acosta et al, 2010), tea fungal biomass (Razmovski and Sciban, 2007); Mesquite (Aldrich et al, 2003), Eucalyptus bark (Sarin and Pant, 2006), red roses waste biomass and Yohimbe bark (Fiol et al, 2008). The present study is undertaken with following objective: Investigate the use of Litchi chinensis Sonn peel for the biosorption of Chromium (VI) in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Various biosorbents have been tried, which include seaweeds, moulds, yeast, bacteria, crab shells, agricultural products such modified corn stalks, (Chen et al, 2011), hazelnut shell (Cimino et al, 2000), orange waste (Perez-Marin et al, 2007) and tamarind peel (Acosta et al, 2010). It has also been reported that some of these biomass can reduce chromium (VI) to chromium (III), like tamarind peel (Acosta et al, 2010), tea fungal biomass (Razmovski and Sciban, 2007); Mesquite (Aldrich et al, 2003), Eucalyptus bark (Sarin and Pant, 2006), red roses waste biomass and Yohimbe bark (Fiol et al, 2008). The present study is undertaken with following objective: Investigate the use of Litchi chinensis Sonn peel for the biosorption of Chromium (VI) in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2010). It has also been reported that some of these biomasses can reduce chromium (VI) to chromium (III), like tea fungal biomass (Razmovski, and Sciban, 2007); Mesquite (Aldrich et. al., 2003), Eucalyptus bark (Sarin and Pant, 2006), red roses waste biomass , Yohimbe bark (Fiol et.…”
Section: Introductionmentioning
confidence: 99%
“…Various biosorbents have been tried, which include seaweeds, molds, yeast, bacteria, crab shells, agricultural products such modified corn stalks, [9], hazelnut shell [10], orange waste [11] and tamarind peel [12]. It has also been reported that some of these biomass can reduce chromium (VI) to chromium (III), like Litchii cinensis Sonn peel [13], tea fungal biomass [14], Mesquite [15], Eucalyptus bark [16], red rose's waste biomass [17] and Yohimbe bark [18]. The present study is undertaken with following objective: Investigate the use of different natural biomasses for the biosorption and reduction of Chromium (VI) in aqueous solution, and their elimination from contaminated sites.…”
Section: Introductionmentioning
confidence: 99%